Cultural Factors and Knowledge of Pregnant Women ANC Visiting Behavior of Indigenous Papuans in the Work Area Mopah Baru Health Center, Merauke Regency - Sihombing, Novi Irmawati; Retnaningtyas, Erma; Muslichah , Miftakul; Angelius Suharto, Hans (Institute Of Computer Science (IOCS), 2024)
Fulfilling the ANC Visit Coverage Target is influenced by Knowledge and Cultural Factors. This study aims to determine the relationship between cultural factors and knowledge of pregnant women on ANC visit behavior of Indegenous Papuans in the working area of ??the Mopah Baru Merauke Community Health Center in 2023. This research design uses cross sectional observational analysis. Using the total sampling technique, a sample of 60 native Papuan pregnant women was obtained. The independent variable (Culture and Knowledge Factors), the dependent variable (ANC Visit Behavior) used a questionnaire. Using the Chi Square statistical test. The research results from 60 respondents mostly had a positive culture, namely 33 respondents (55%), most respondents had poor knowledge, 34 respondents (56.7%), and most respondents had negative ANC visit behavior, 32 respondents (53). .3%). There is no relationship between cultural factors of pregnant women on ANC visit behavior with p value = 0.061 > 0.05 and there is a relationship between knowledge of pregnant women on ANC visit behavior, namely p value = 0.011 < 0.05. There is a need to increase the role of midwives to increase the coverage of ANC visits for pregnant women, especially Indigenous Papuan pregnant women.